Genetic dissection of seedling traits in a BC4F3 population under the stress of cadmium in sweet corn - Haoxuan Jiang; Yanchao Du; Jianting Lin; Huating Zhao; Xiaming Wu; Faqiang Feng (Euphytica, 2026)

Dynamic valuation of the provisioning services of marine fisheries ecosystem based on BeiDou VMS data: A case study of TACs project for Acetes chinensis in the Yellow Sea - Guodong Li; Dongjia Li; Ying Xiong; Xiaming Zhong; Jinjin Shi; Hushun Zhang; Dade Song; Fan Yang; Zhongjie Kang; Xiaorui Wu; Shuyan Wang; Long Liang (Ocean & Coastal Management, 2023)

Changes in overwintering ground of small yellow croaker ( Larimichthys polyactis ) based on MaxEnt and GARP models: A case study of the southern Yellow Sea stock - Guodong Li; Ying Xiong; Xiaming Zhong; Dade Song; Zhongjie Kang; Dongjia Li; Jianhua Tang; Yanping Wang; Lei Wu (Journal of Fish Biology, 2023)
Small yellow croaker ( Larimichthys polyactis ), a commercially essential fish commonly caught in China and South Korea, is now facing a severe decline in resources. The recruitment and surplus of L. polyactis depend selecting a suitable marine environment for overwintering. However, the international overwintering migration habit of L. polyactis limits the investigation of its overwintering environment preferences and suitable grounds. In this study, based on the distribution data of L. polyactis in the southern Yellow Sea in winter from 2010 to 2019 and ocean remote sensing data such as sea bottom temperature (SBT), sea bottom salinity, chlorophyll‐a concentration and water depth (Depth), we used the maximum entropy (MaxEnt) and the genetic algorithm for rule‐set production (GARP) models to investigate the overwintering grounds of the southern Yellow Sea stock (SYS). The jackknife test was used to assess the importance of various environmental factors. For modelling the overwintering ground distribution of SYS, the area under the curve values of both models ​were higher than 0.9. The overwintering ground was at 32°10′ N–33°48′ N, 122°30′ E–125°00′ E. The direction of its distribution was consistent with the Yellow Sea Warm Current in the southern Yellow Sea during the winter. Compared with the suitable overwintering area during 2010–2014, the highly appropriate overwintering area for SYS to overwinter decreased significantly during 2015–2019, showing a trend of moving to the east and north, related to the increase in fishing pressure and strengthening of the Yellow Sea Warm Current in recent years. Depth was the most significant factor for SYS overwintering, followed by SBT. The overwintering ground was at a depth of 40–65 m during the two periods. Additionally, the suitability of overwintering grounds in the coastal waters of south‐western South Korea has gradually increased. This study provides a scientific basis for formulating effective strategies to manage L. polyactis resources under the China–South Korea Fisheries Agreement.

Influence of relative thickness on static and dynamic stall characteristics and prediction of airfoils - Pengzhong Wang; Lu Wang; Xiaming Kong; Dazhuan Wu; Bin Huang (Ocean Engineering, 2023)